Ukarā - Theodosius, 1st cent. B.C (Sarasvatībhavana-granthamālā, 1978)
On spherical geometry; Greek considerations adapted to Hindu mathematics and astrology through Arabic translated into Sanskrit by Nayanasukhopādhyāya from the Arabic version of the Greek original.